TRABALHO E PROTEÇÃO SOCIAL NO BRASIL: TENDÊNCIAS E RECONFIGURAÇÕES NO CAPITALISMO CONTEMPORÂNEO (REVISTA DIREITOS, TRABALHO E POLÍTICA SOCIAL, 2017)
Este artigo trata numa perspectiva crítica sobre as mutações que ocorrem no mundo do trabalho com o desenvolvimento da sociedade capitalista, especificamente a partir do contexto da crise do capital e as implicações deste processo na implementação das políticas de proteção social, dada a intrínseca relação entre esta e o trabalho na sociabilidade capitalista. O texto problematiza também acerca da constituição e dos limites da proteção social na particularidade brasileira, uma vez que este sistema nunca se configurou como um modelo universalizante de seguridade social e das suas tendências na contemporaneidade. WORK AND SOCIAL PROTECTION IN BRAZIL: TRENDS AND RECONFIGURATIONS IN CONTEMPORARY CAPITALISMAbstract: This article deals with a critical perspective on the mutations that occur in the world of work with the development of capitalist society, specifically from the context of the crisis of capital and the implications of this process in the implementation of social protection policies, given the intrinsic relation between this and the work in capitalist sociability. The text also discusses the constitution and limits of social protection in Brazilian particularity, since this system has never been configured as a universalizing model of social security and its trends in the contemporary world.Keywords: Work. Capital crisis. Social protection.